Non-catalytic heteroepitaxial growth of aligned, large-sized hexagonal boron nitride single-crystals on graphite. Issue 18 (6th May 2020) - Arai, Hayato; Inoue, Taiki; Xiang, Rong; Maruyama, Shigeo; Chiashi, Shohei
Abstract : Large-sized and well aligned h-BN single-crystals were grown on graphite without metal catalysts. Abstract : Although van der Waals heterostructures composed of graphene and hexagonal boron nitride (h-BN) have attracted wide interest, it is still challenging to prepare them with high quality and controllability. Since contamination induced by transfer cannot be avoided in the case of growth on a metal catalyst, the non-catalytic growth of graphene and h-BN is highly desired. However, unlike graphene, few studies have reported the non-catalytic growth of h-BN, and the lack of controllability in terms of crystal orientation and nucleation density, and size of h-BN has hindered the practical applications of the heterostructures. In this work, we demonstrate the heteroepitaxial growth of aligned monolayer h-BN single-crystals on exfoliated graphite by chemical vapour deposition (CVD) without a metal catalyst. Triangular shaped domains were aligned with each other, which suggests the epitaxy between h-BN and the underlying graphite. Characterisation by Raman spectroscopy, Auger electron spectroscopy, and X-ray photoelectron spectroscopy also confirmed that the h-BN/graphite samples were of high quality. A growth kinetics study over different temperatures indicated an increase in the growth rate at high temperature. Control of nucleation density was realised by changing the hydrogen pressure during CVD or by the heating temperature in air before CVD. Under the optimised growth conditions, the edge length of h-BN single-crystals grew to ∼1 μm, which is the largest size to date for non-catalytic growth. These results will help to obtain structure-controlled, large-area, and impurity-free heterostructures based on h-BN and graphene.